Gawai Naik Dango As A Material Of Respect To Ene' Daniang Dayak Bukit Tribe West Kalimantan - Anjelinus Loi; Dismas Kwirinus; Heribertus Peri (Equilibrium: Jurnal Pendidikan, 2023)
The focus of this research examines the Gawai Naik Dango as a Respect Ceremony for Ene' Daniang of the Dayak Bukit Tribe of West Kalimantan. The topic of study is related to ritual issues and ceremonies of respect for Ene' Daniang as the Highest Being of the Bukit Dayak tribe. The gawai Naik Dango ritual ceremony is seen as a very important ceremony, it underlies all other ceremonies, both private and collective. All family members gather to hold the rituals of Nyangahatn Mati, Nyangahatn Ka' Sami, Nyangahatn Ka' Padarengan, Nyangahatn Ka' Dango Padi; they also held sacrifices and offerings to the Highest Being, Ene' Daniang through the intercession of the ancestors accompanied by singing and dancing, and culminating in a festive party together at the traditional house. The researcher uses descriptive qualitative methods and critical reading of texts, namely: (1) Cultural philosophy books related to understanding the concept of the Supreme Being; (2) Articles that concentrate on studying the concept of the Naik Dango traditional ceremony. The findings in this study are that the concept of the Highest Being, Ene' Daniang in the Bukit Dayak community, is embodied in customs, customary law, language, and art. In short, it is contained in every aspect of human life. They farm, for example, not only as a fulfillment of economic needs, but also as an implementation of Ene' Daniang's will and to bring back Ene' Daniang's actions to humans. Rice is a gift from Ene' Daniang which must be replanted from generation to generation through farming. The way to plant and harvest it does not just happen, but through various ceremonies (rituals), such as Ngawah, Ngalabuhatn, Ngaladakng Buntikng Padi, Ngabati, Ngaleko, Nabo' Panyugu Nagari, and Panyugu Tahutn or Naik Dango.